A narrative inquiry into primary caregivers' understanding of their child's psychological assessment : a thesis presented in partial fulfilment for the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, Auckland, New Zealand - Niemand, Jessica; Niemand, Jessica (Massey University, 2010)
This study explores the ways in which primary caregivers experience the process of having their child psychologically assessed. The research uses a narrative methodology to explore the accounts of seven participants who have supported their child through a process of psychological assessment. Caregivers were interviewed and their interviews were transcribed and analysed by outlining the sequential order of events and the main themes of each of the participants’ narratives. Individual stories were then combined to present the overarching themes that emerged from the study. The main themes include the following: suspected “diagnosis” and own expertise, seeing “inside” the child, bittersweet labels, questions of guilt and blame, the “good parent”, the distant professionals, problems with communication, challenging the system, inadequate measures, over-assessed, caregiver as the defender and advocate and the helpful professional. This research contributes to the limited literature on client’s perspectives of psychological intervention and is intended to improve clinicians understanding of this area.
Keywords: Primary caregivers; Parents; Psychological testing